Ta'lim Al-Hiwar Bi Istikhdam Thariqah Socrates - Ubaid Ridlo; Muhamad Hasby Ashidiqi (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2021)
This research aimed that Socrates method in learning dialogue can increase class effectiveness. This research is a mix method (qualitative and quantitative) by using the classroom action research method with Kurt Lewin’s Model. It has four steps that the researcher must follow, including planning, implementation, observation, and reflection in each role. Through this, data is collected on the following methods: observation, interview, and documentation. The lack of participation and exchange of opinions between the students, each other, during the lesson, and their weakness in presenting ideas and their critical stances on the subject. This indicates that the classroom interaction was not effective as represented in the preliminary research. The classroom interaction according to the observation was 46%, and according to him, the researcher conducted the current research. Socrates’ method is of its importance to provoke students' participation in the learning and teaching process, as this method revolves around dialogue with the method of questioning from the same teacher. One of the most important results was that the class interaction rises little by little in view of the first and second rounds. The result of class interaction in the first round got 58% and in the second round 65% with an increase of 8%. Through this, it can be said that the use of the Socrates method in learning dialogue can increase class effectiveness.